The changing face of newspaper representations of the mentally ill. (2013) - Murphy, Neil A.; Fatoye, Francis; Wibberley, Christopher
Abstract : Background: Negative stereotypes presented in the media may contribute to the stigma associated with mental illness. People's attitudes towards the mentally ill are initially influenced and subsequently maintained in part by the frequent media presentation of negative stereotypes of mental illness. This could result in social rejection of individuals with mental illnesses. Aim: To explore how four main UK national newspapers reported on mental health/mental illness stories over a 10-year period. Method: This study utilised content analysis to identify words, themes and trends of representation related to the mentally ill in articles from the four newspapers. Results: The findings indicated that there was an increase in the number of articles related to mental health/illness over the time of the study. The rate of increase was far greater than that for the increase in the total number of articles carried in the press over this time period. It was also identified that pejorative terms were used, in a number of the articles, to describe the mentally ill person. Conclusion: Many of the newspaper reports highlighted the need for protection of the general public from the mentally ill, and that the mentally ill were in some way different to the general public. In particular, both the words "violence" and "drugs" were linked to mental health/mental illness in these articles.